Synthesis of linear sparse arrays based on dynamic parameters differential evolution algorithm. Issue 9 (23rd May 2019) - Wang, Xujian; Yao, Minli; Dai, Dingcheng; Zhang, Fenggan
Abstract : Synthesis of antenna arrays is a momentous technology possessing many advantages and broad prospects. Dynamic parameters differential evolution (DPDE) with two modifications is proposed for the synthesis of linear sparse arrays (LSA) which aims at reducing peak side‐lobe level. One modification is that the scaling factor decreases monotonically over iterations, making exploration in the later period more efficient and accuracy. The other modification is that the crossover probability changes dynamically during iterative process through a novel self‐adaptive strategy. Experiments of checking on benchmark functions and simulations of synthesising LSA validate that DPDE performs better than reference methods convincingly.